Synchronization by the Grace of God? The Film/Music Collaboration of Jean Cocteau and Georges Auric - Deaville, James; Wood, Simon (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2001)
Jean Cocteau's relationship with music has never been explored in detail with regard to his films. Given his well-known statements against synchronization, Cocteau appears upon first glance not to have paid much attention to the relationship between image, word and music, entrusting the music to his long-term friend Georges Auric. However, a closer examination of Auric's scores in the context of their films reveals a much closer corraboration of music and film than previously thought by specialists (or admitted by Cocteau). Analysis of musical and filmic elements in Le Sang d'un poète (1932), La Belle et la Bête (1946) and Orphée (1949) presents a complex and rich yet traditional approach to film scoring both by Auric and Cocteau.